TARI CAMPAK BUNGA PADA MASYARAKAT MELAYU SERDANG KAJIAN ETIKA - Maulina - Astari; Rhd - Nugrahaningsih (Universitas Negeri Medan, 2019)
ABSTRACT This study aims to describe how ethics exist in the Campak Bunga dance in the Malay community of Serdang. The theoretical foundation in this paper is used as a guideline in data collection consisting of Malay Serdang people and Ethics which are used as references in conducting this research. The technique of collecting data is done by observation, interview, literature study and documentation. Observations were carried out such as the form of Measles of Flower dance, recording the results of interviews and carrying out video and photo documentation. Continuing to review every ethic that exists in Measles Flower Dance in accordance with the theory used. The method used in this study is a qualitative descriptive method where the data obtained by the author is carefully processed and analyzed. the processed results and analysis are compiled so as to produce reports in the form of writing or thesis. The results of the study show that ethics in dance Flower Measures are seen from moral norms in Measles Dance Flowers are illustrated through motion and clothing. From the side of motion how this dance is performed by starting through the opening greetings and ending it with the closing greetings. In terms of fashion shows that through the long kebaya and sarong worn by princess dancers, as well as bay belanga, songket cloth and cap. The courtesy norm is illustrated by the variety of motion of motion, mercy, sowing of flowers, croaking or saok, cucuk and elak, sweet black. Norms of Religion in all kinds of movements from beginning to end. Keywords: Measles Dance flower, Serdang Malay, Studies Ethics ABSTRAKPenelitian ini bertujuan untuk mendeskripsikan bagaimana etika yang ada pada tari Campak Bunga pada masyarakat Melayu Serdang. Landasan teoritis dalam artikel ini dijadikan pedoman dalam pengumpulan data terdiri dari masyarakat Melayu Serdang dan Etika yang dijadikan acuan dalam melakukan penelitian ini. Teknik pengumpulan data dilakukan dengan cara observasi, wawancara, studi kepustakaan dan dokumentasi. Observasi yang dilakukan seperti bentuk tari Campak Bunga, merekam hasil wawancara dan melakukan dokumentasi video dan foto. Dilanjutkan mengkaji setiap etika yang ada pada Tari Campak Bunga sesuai dengan teori yang digunakan. Metode yang digunakan dalam penelitian ini yaitu metode deskriptif kualitatif dimana data yang diperoleh penulis diolah dan dianalisis dengan teliti. hasil olahan dan analisis tersebut disusun sehingga menghasilkan laporan dalam bentuk tulisan atau artikel jurnal. Hasil penelitian menunjukan bahwa etika pada tari Campak bunga dilihat dari norma susila dalam Tari Campak Bunga tergambar melalui gerak dan busana. Dari sisi gerak bagaimana Tari ini dipertunjukkan dengan memulainya melalui salam pembuka dan mengakhirinya dengan gerak salam penutup. Dari sisi busana menunjukkan bahwa melalui kebaya panjang dan sarung yang dikenakan penari putri, serta teluk belanga, kain songket dan peci. Norma Kesopanan tergambar melalui ragam gerak melenggang, elak, tabur bunga, kuak atau saok, cucuk dan elak, hitam manis. Norma Agama dalam seluruh ragam gerak dari awal hingga akhir. Keywords: Tari Campak Bunga, Melayu Serdang, Kajian Etika